Un nouveau souffle pour les consorteries de la Vallée d’Aoste - Roberto Louvin; Nicolò P. Alessi (Revue de Géographie Alpine)
Commons have existed in the Aosta Valley’s territory for centuries, of which the most distinguishing and still lively are called “Consorterie”. This article aims to study this peculiar form of commons, as well as the evolution of their legal status, focusing on national and regional legislation. This paper also seeks to analyse a regional draft bill on commons written by a technical group appointed by the regional government. Its principal goal is to provide Consorterie with a new legal status in line with the results achieved by scholars, jurisprudence and national legislation. Moreover, the legislative proposal explores the regional legislative competence related thereto by proposing some innovative solutions.